Characterization of circulating tumor cells in early breast cancer patients receiving neoadjuvant chemotherapy. (July 2021) - Jakabova, Anna; Bielcikova, Zuzana; Pospisilova, Eliska; Petruzelka, Lubos; Blasiak, Piotr; Bobek, Vladimir; Kolostova, Katarina
Background and Aims: The aim of this study was to characterize circulating tumor cells (CTCs) during neoadjuvant chemotherapy (NACT) in early and locally advanced breast cancer (LABC) patients. Using ultrasound, tumor volume measurement was compared with the presence and the molecular nature of CTCs over multiple time intervals corresponding to treatment periods. Methods: A total of 20 patients diagnosed with breast cancer (BC) of different histotypes were monitored during the NACT period and in the follow-up period (~5 years). Peripheral blood for CTCs ( n  = 115) was taken prior to NACT, after two to three chemotherapy cycles, after the completion of NACT (before surgery) and at some time points during adjuvant therapy. CTCs were enriched using a size-based filtration method (MetaCell®) capturing viable cells, which enabled vital fluorescence microscopy. A set of tumor-associated (TA) genes and chemoresistance-associated (CA) genes was analyzed by qPCR in the enriched CTC fractions. Results: The analysis of tumor volume reduction after administration of anthracyclines (AC) and taxanes (TAX) during NACT showed that AC therapy was responsive in 60% (12/20) of tumors, whereas TAX therapy was responsive in 30% (6/20; n.s.). After NACT, CTCs were still present in 70.5% (12/17) of patients (responders versus non-responders, 61.5% versus 100%; not significant). In triple-negative BC (TNBC) patients ( n  = 8), tumor volume reduction was observed in 75% cases. CTCs were significantly reduced in 42.9% of all HER2-negative BC patients. In HER2+ tumors, CTC reduction was reported in 16.6% only. Relapses were also more prevalent in the HER2-positive patient group (28.5 versus 66.6%). During NACT, the presence of CTCs (three tests for each patient) identified patients with relapses and indicated significantly shorter progression-free survival (PFS) rates ( p  = 0.03). Differentiation between progressive disease and non-progressive disease was obtained when the occurrence of excessive expression for CA genes in CTCs was compared ( p  = 0.024). Absence of tumor volume reduction was also significantly indicative for progressive disease ( p  = 0.0224). Disseminated CTCs in HER2-negative tumors expressed HER2 in 29% of samples collected during the overall follow-up period (16/55), and in 32% of samples during the follow-up of NACT (10/31). The change accounted for 78.5% of HER2-negative patients (11/14) in total, and 63.6% of the conversion cases occurred during NACT (7/11). For the remaining four patients (36.3%), conversion to HER2+ CTCs occurred later during adjuvant therapy. We believe there is the possibility of preventing further progression by identifying less responsive tumors during NACT using CTC monitoring, which could also be used effectively during adjuvant therapy.